2018
DOI: 10.3389/fpsyg.2018.02263
|View full text |Cite
|
Sign up to set email alerts
|

Reading Instructions Influence Cognitive Processes of Illustrated Text Reading Not Subject Perception: An Eye-Tracking Study

Abstract: Scientific illustrations play an important role in scientific texts, however, young readers show limited ability to use illustration information and integrate it with the text in multimedia learning. The primary goal of the present study was to investigate if strategy instructions for illustrated text reading focused on scientific illustration reading and text-illustration integration can help young readers overcome their deficiencies and change their reading processes, learning outcomes, and subjective percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Students with better scores in reading speed and reading comprehension also had higher scores in perception skills. Furthermore, it has been shown that reading is heavily text-driven for young readers (Jian, 2016), while strategy instructions for reading illustrated texts promote reading comprehension and change learning processes for older readers (Jian, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Students with better scores in reading speed and reading comprehension also had higher scores in perception skills. Furthermore, it has been shown that reading is heavily text-driven for young readers (Jian, 2016), while strategy instructions for reading illustrated texts promote reading comprehension and change learning processes for older readers (Jian, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, reading as a cognitive process of constructing knowledge through meaning negotiation (Jian, 2018) is a multifaceted activity that is done through reader-and-text interactions within a given context (Jiménez et al, 2009;van den Broek, 2012). This is in line with the efforts of enhancing comprehension in reading that covers active processes by which students focus on their prior knowledge, vocabularies, inference, and comprehension monitoring skills (Elleman & Oslund, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Motivation plays an important role in science students' reading by determining the extent to which students engage with science texts and persevere in applying effort, without aborting, until successfully completing the texts' accompanying reading comprehension tasks (see review by Morgan and Fuchs, 2007). Thus, when facing a reading task, students must not only attain knowledge about reading comprehension strategies such as locating ideas in text and processing and integrating information-namely, cognitive self-regulation skills-but also must attain knowledge about how and when to apply these different cognitive strategies-namely, metacognitive self-regulation skills (e.g., Schreiber, 2005;Roebers, 2017;Jian, 2018;Pamungkas et al, 2018;Farhana et al, 2020). Students must also acquire explicit strategies for self-regulating their own motivation-deciding how to approach the knowledge acquisition process and how much effort to invest-to cope with what may be a cognitively, emotionally, and temporally demanding task (e.g., McClelland et al, 2007;Guthrie and Coddington, 2009;Kelley and Decker, 2009;Logan et al, 2011;Skibbe et al, 2011;Liew et al, 2019;Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%